Hypertension and Its Association with Noise Exposure among Blacksmith Workers in an Indonesian Village - Christopher F. Jaya; Marsen Isbayuputra; Jenny Bashiruddin; Dewi Sumaryani Soemarko; Rino Alvani Gani (The Indonesian Journal of Community and Occupational Medicine, 2026)
Background: Blacksmith workers are at high risk of hypertension due to occupational exposures such as noise, heat, and heavy physical activity. Although noise exposure has been linked to cardiovascular stress through sympathetic activation, evidence regarding its direct association with hypertension in informal workers remains limited.Objective: To determine the prevalence of hypertension and its associated factors among blacksmith workers in an Indonesian village and to identify whether occupational noise exposure contributes to increased blood pressure.Methods: This was an analytical observational study with a cross-sectional design involving 107 blacksmith workers. Data were collected through interviews, blood pressure measurements, noise level assessment using a sound level meter, and body mass index (BMI) calculation. Bivariate analysis used Chi-square and Mann–Whitney tests, while multivariate analysis used logistic regression.Results: The prevalence of hypertension was 34.5%. Bivariate analysis showed significant associations between noise intensity (p=0.008), age (p=0.001), working duration (p=0.042), smoking degree (p=0.002), and BMI (p<0.001) with hypertension, whereas noise type was not significant (p>0.05). In multivariate analysis, only BMI remained significant (aOR=2; 95% CI: 1.3–3.3).Conclusion: The prevalence of hypertension was 34.5%. BMI is an independent risk factor for hypertension among blacksmith workers. Noise exposure was not significantly associated with increased blood pressure, likely due to confounding effects and non-differential noise types. Interventions should focus on weight management and regular blood pressure monitoring in this worker population.